2019
DOI: 10.1021/acsaem.9b00733
|View full text |Cite
|
Sign up to set email alerts
|

ZIF 67 Based Highly Active Electrocatalysts as Oxygen Electrodes in Water Electrolyzer

Abstract: Mitigating high overpotential losses originating from the sluggish oxygen evolution reaction (OER) during water electrolysis is key to establishing a sustainable hydrogen generation technique. Herein we report a Co-imidazolate framework (ZIF 67) as an OER catalyst that exhibits high activity in both a three electrode cell and an electrolyzer. Additionally, Fe, Ni, and Zn have been incorporated into ZIF 67 to evaluate their effects on the OER activity of ZIF 67. Due to the high charge conductivity of ZIF 67, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 46 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…Based on such guidelines, various MOF-based electrocatalysts have been designed to achieve superior performances in electrocatalysis . Especially, because of the importance of the oxygen evolution reaction (OER) in water splitting, Co-MOFs, , NiCo-MOFs, FeCo-MOFs, , and NiFe-MOFs , have been extensively explored, and all of them imply the atomic metal nodes as the real active sites for oxygen production.…”
Section: Introductionmentioning
confidence: 99%
“…Based on such guidelines, various MOF-based electrocatalysts have been designed to achieve superior performances in electrocatalysis . Especially, because of the importance of the oxygen evolution reaction (OER) in water splitting, Co-MOFs, , NiCo-MOFs, FeCo-MOFs, , and NiFe-MOFs , have been extensively explored, and all of them imply the atomic metal nodes as the real active sites for oxygen production.…”
Section: Introductionmentioning
confidence: 99%
“…S2a, † which is in good accordance with the simulated diffraction pattern reported in the literature, indicating the successful formation of the ZIF-67 structure. 36 Hollow Ru-ZIF-67 was successively synthesized by a simple ion-assisted etching method using the previously synthesized ZIF-67 as a template, as shown in Fig. 1a.…”
Section: Resultsmentioning
confidence: 99%
“…42 Another example is a recent study by us regarding the electrochemical instability of ZIF-67 (Figure 4A), 19 a commonly used MOF "electrocatalyst" claimed to be stable and OER-active. 43 Comprehensive analysis revealed that the ZIF-67 could not retain its structure even in mild electrochemical tests (Figure 4B,C). Using in situ Raman and UV−vis spectroscopies, the ZIF-67 was shown to irreversibly transform into OER-active α-Co(OH) 2 and β-Co(OH) 2 , and longer reaction time or higher overpotential led to a quicker collapse of the structure (Figure 4D).…”
Section: Metrics and Morementioning
confidence: 99%
“…Another example is a recent study by us regarding the electrochemical instability of ZIF-67 (Figure A), a commonly used MOF “electrocatalyst” claimed to be stable and OER-active . Comprehensive analysis revealed that the ZIF-67 could not retain its structure even in mild electrochemical tests (Figure B,C).…”
mentioning
confidence: 99%